Design of amplifiers using organic printed electronics - Tan, See Youu. (2009)
Organic electronics is a branch of electronics that deals with conductive polymers, plastics, or small molecules. This technology had merged with the technology of printed electronics. It is defined as printing of electronics on common media such as paper, plastic, and textile using standard printing process. The advantages of this new technology included low cost, and flexibility of electronics circuit.